Deskripsi Pengembangan Kurikulum Pembelajaran Bahasa Arab Di Malaysia - Hidayatul Khoiriyah (LP2M IAIN Sultan Amai Gorontalo, 2020)
The purpose of this study is to describe the education system and find out the Arabic learning curriculum in Malaysia in terms of objectives, methods, and evaluation. This research is a research in the form of library research that is qualitative in nature and takes the object of curriculum research documents in Arabic learning in Malaysia. The data used as a source of writing are archives from the Ministry of Education of Malaysia which are accessed by internet, and several articles relating to the study. The results of the study indicate that the Arabic language learning curriculum in Malaysia aims to have four language skills, but has not yet reached the stage of interacting and communicating, both verbally and in writing. The method used in Malaysia is the inquiry method, cooperative, etc. Evaluation in Malaysia’s curriculum system was carried out through summative and formative assessments.